Voriconazole‐Associated Periostitis: New Insights into Pathophysiology and Management. (6th October 2021) - Bennett, Michael J; Balcerek, Matthew I; Lewis, Edward AD; Zhang, Roland LL; Bachmeier, Caroline; Tey, Siok; Faux, Steven; Girgis, Laila; Greenfield, Jerry R; Lazarus, Syndia
ABSTRACT: Voriconazole‐associated periostitis (VAP) is an underrecognized and unpredictable side effect of long‐term voriconazole therapy. We report two cases of VAP occurring in the post‐transplant setting: a 68‐year‐old lung transplant recipient who required ongoing voriconazole therapy, in whom urinary alkalinization was used to promote fluoride excretion and minimize voriconazole‐related skeletal toxicity, and a 68‐year‐old stem‐cell transplant recipient with a high voriconazole dose requirement, identified on pharmacogenomic testing to be a CYP2C19 ultrarapid metabolizer, the dominant enzyme in voriconazole metabolism. This is the first reported case of pharmacogenomic profiling in VAP and may explain the variability in individual susceptibility to this uncommon adverse effect. Our findings provide new insights into both the management and underlying pathophysiology of VAP. © 2021 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.